Handbook of Evidence-Based Mental Health Practice With Sexual and Gender Minorities 2019
DOI: 10.1093/med-psych/9780190669300.003.0019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-Focused Therapy for Sexual and Gender Minority Individuals and Their Parents

Abstract: This chapter describes the negative impact that ongoing parental rejection can have on sexual and gender minority individuals and the importance of promoting parental acceptance. It then introduces and describes the structure and intervention strategies of relationship-focused therapy—a time-limited, experiential, family-based treatment specifically designed to increase parental acceptance, reduce parental rejection, and help sexual and gender minority individuals and their parents re-establish or develop lovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In contrast, those parents who showed no such increases in RF over the same timeframe reported poor agreement with such treatment goals. These findings point to the potential importance and utility of facilitating parental reflectivity before attempting to enlist parents in the attachment task, and are consistent with ABFT theory and practice (G. M. Diamond et al, 2019; G. S. Diamond et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, those parents who showed no such increases in RF over the same timeframe reported poor agreement with such treatment goals. These findings point to the potential importance and utility of facilitating parental reflectivity before attempting to enlist parents in the attachment task, and are consistent with ABFT theory and practice (G. M. Diamond et al, 2019; G. S. Diamond et al, 2014).…”
Section: Discussionsupporting
confidence: 78%
“…One treatment specifically developed to decrease parental rejection, improve parental acceptance, and repair attachment bonds among SGM young adults and their nonaccepting parents is attachment‐based family therapy for sexual and gender minorities (ABFT‐SGM; G. M. Diamond et al, 2019). ABFT‐SGM was adapted from ABFT for depressed and suicidal adolescents (G. S. Diamond, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Training took place over the course of six months. During the training, therapists read the ABFT‐SGM manual (Diamond & Boruchovitz‐Zamir, in press; Diamond, Boruchovitz‐Zamir, et al, 2019), and clinical papers on working with SGM young adults and their persistently nonaccepting parents (Diamond & Shpigel, 2014). They also watched training tapes exemplifying how to complete each treatment task.…”
Section: Methodsmentioning
confidence: 99%
“…One such treatment is attachment‐based family therapy for sexual and gender minority young adults and their nonaccepting parents (ABFT‐SGM; Diamond & Boruchovitz‐Zamir, in press; Diamond, Boruchovitz‐Zamir, et al, 2019). ABFT‐SGM is a manualized, time‐limited (26 weeks), empirically informed, family‐based treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a pilot open clinical trial showed pre-to posttreatment decreases in attachment anxiety and avoidance among depressed and suicidal lesbian, gay, and bisexual (LGB) adolescents (G. M. Diamond et al, 2012). Preliminary results from a current 5-year open clinical trial suggest that ABFT is associated with significant increases in adult children's perceptions of their parents' acceptance and significant decreases in their perceptions of their parents' rejection, from pre-to posttreatment (G. M. Diamond, 2018).…”
Section: Brief Overview Of Attachment-based Family Therapymentioning
confidence: 99%